Mineral, chemical and isotopic compositions of hydrothermally altered sediments from the Middle Valley (Juan de Fuca Ridge), ODP Site 139-858 - Sylvie Decitre; Martine D Buatier; Rachael H James (PANGAEA, 2004)
Li and Li isotopes have been measured in the clay fraction of sediments recovered from the Middle Valley hydrothermal site on the Juan De Fuca Ridge. The Li content of pure detrital clays is 51 ppm while hydrothermal clays and carbonates have lower Li (22+/-11 ppm). However, there is no clear relationship between the mineralogy of the hydrothermal alteration products and their Li content. The d7Li value of the detrital clays is +5.8 extperthousand. Hydrothermal clays and carbonates have d7Li in the range of -3.9 extperthousand to +7.8 extperthousand; these values do not seem to be dependent on the temperature at which they formed. Modelling of the Li and Li isotope systematics indicates that the fluid from which the alteration products form is significantly enriched in Li (higher than 10000 μmol/kg) relative to pore fluids recovered from within the sediments (up to 589 μmol/kg; [Wheat, C.G., M.J. Mottl, 1994. Data report: trace metal composition of pore water from Sites 855 through 858, Middle valley, Juan De Fuca Ridge. In Mottl, M.J., Davis, E.E., Fisher, A.T., Slack, J.F. (Eds.), Proc. ODP, Sci. Res. 139: 749–755; doi:10.2973/odp.proc.sr.139.269.1994]), and that this Li is derived from sediment. Thus, the alteration products are not in equilibrium with their conjugate pore fluids; rather, the alteration minerals formed at lower water/sediment ratios. This suggests that fluid flow pathways at Middle Valley were more diffuse in the past than they are today.
Supplement to: Decitre, S et al. (2004): Li and Li isotopic composition of hydrothermally altered sediments at Middle Valley, Juan De Fuca. Chemical Geology, 211(3-4), 363-373, https://doi.org/10.1016/j.chemgeo.2004.07.005